2019
DOI: 10.3389/fmicb.2019.00815
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Patterns of Human and Avian Influenza Viruses to Trachea and Colon of 26 Bird Species – Support for the Community Concept

Abstract: Avian influenza A viruses (AIVs) have a broad host range, but are most intimately associated with waterfowl (Anseriformes) and, in the case of the H13 and H16 subtypes, gulls (Charadriiformes). Host associations are multifactorial, but a key factor is the ability of the virus to bind host cell receptors and thereby initiate infection. The current study aims at investigating the tissue attachment pattern of a panel of AIVs, comprising H3N2, H6N1, H12N5, and H16N3, to avian trachea and colon tissue samples obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
(133 reference statements)
3
14
0
Order By: Relevance
“…Surface adhesion is achieved by binding HA to the cellular SA receptors. Although virus histochemistry only provides information about viral HA for host cell surface adhesion rather than replication ability of virus, it should be highlighted that viral HA for host cell surface adhesion is a necessary condition in the virus replication cycle [42]. In this study, the capacities of IAV bound with SA receptors in the airway of HBV-transgenic mice model and control mice were assessed, which showed that there were more H5N1 subtype strain virus and H1N1 vaccine binding to the trachea tissues from 14 to 16 or 18 month old HBV-transgenic mice compared with control mice significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Surface adhesion is achieved by binding HA to the cellular SA receptors. Although virus histochemistry only provides information about viral HA for host cell surface adhesion rather than replication ability of virus, it should be highlighted that viral HA for host cell surface adhesion is a necessary condition in the virus replication cycle [42]. In this study, the capacities of IAV bound with SA receptors in the airway of HBV-transgenic mice model and control mice were assessed, which showed that there were more H5N1 subtype strain virus and H1N1 vaccine binding to the trachea tissues from 14 to 16 or 18 month old HBV-transgenic mice compared with control mice significantly.…”
Section: Discussionmentioning
confidence: 99%
“…SA α2,3-Gal is the dominant receptor type in the intestines of these birds, and presence of both SAα2,3-Gal β(1-3)GalNAc and SAα2,3-Gal β(1-4)Glc NAc has been identified [ 21 ]. SA expression is reported to vary among various species of this order [ 66 ].…”
Section: Distribution Of Sialic Acid Receptors Among Multiple Hostmentioning
confidence: 99%
“…Of the type of SA α2,3-Gal receptors, SAα2,3-Gal β(1-4) GlcNAc receptors were reported to be dominant in these birds [ 21 ]. However, inter-species variations in the SA expression among the birds of this order have been reported [ 66 ].…”
Section: Distribution Of Sialic Acid Receptors Among Multiple Hostmentioning
confidence: 99%
“…It was important to investigate AIV attachment to trachea in many avian species [19]. AIVs mainly attached to α2,3-linked SA, but also to combinations of α2,3and α2,6-linked SA [20].…”
Section: Introductionmentioning
confidence: 99%